Cytoplasmic Ribonucleoprotein Foci in Eukaryotes: Hotspots of Bio(chemical)Diversity. (27th May 2012) - Layana, Carla; Ferrero, Paola; Rivera-Pomar, Rolando
Abstract : The life of an mRNA from transcription to degradation offers multiple control check points that regulate gene expression. Transcription, splicing, and translation have been widely studied for many years; however, in recent years, new layers of posttranscriptional and posttranslational control have been uncovered. They involve the regulation of the metabolism of mRNA in cytoplasmic foci. They are collections of ribonucleoprotein complexes that, in most cases, remain still uncharacterized, except the processing bodies (PBs) and stress granules (SGs), which have been studied (and reviewed) in detail. A challenging prospective is to know how many different classes of foci exist, which functions they support, how are they formed, and how do they relate one to each other. Here, we present an update of the component of the different granules, a possible function, and hypothesis on their in vivo dynamics related to translational control.